Keberkesanan Pengaplikasian Revit dalam Industri Pembinaan - Sudin, Ahmad Syakir Aiman; Mohamed, Sulzakimin; Ta Wee, Seow; Kai Chen, Goh; Masrom, Md Asrul Nasid; Abd Rahim, Mohd Hilmi Izwan (Research in Management of Technology and Business, 2021)
Autodesk Revit software is software found in the Building Information Modeling (BIM) method which is used to design a construction project. The BIM method is a new approach in construction design. This is because this method not only facilitates digital presentation for the design but also provides all the information needed for each construction project. The use of Building Information Modeling method was introduced for the first time in Malaysia in 2007 by the Director of the Public Works Department (JKR). The introduction of this method was extended when the government realized that the use of BIM has many benefits to the country. This is because the use of BIM can overcome the problem of project construction at an early stage. The use of BIM can usually be distinguished by material consumption, construction period and marketing cost. The BIM method uses several types of software such as Revit Architecture and Inventor from Autodesk. The use of Autodesk Revit software which is one of the applications in the BIM method can help facility management to plan, collect information and manage a facility more effectively. Therefore, this study was conducted to investigate the effectiveness of the implementation of Autodesk Revit software in the construction industry in Malaysia. The study also compared the level of construction projects using Autodesk Revit software with traditional construction methods. The methodology used in this study is a literature review, observations and interviews with 3 G7 contractors in the Federal Territory of Kuala Lumpur. The result shows the implementation of this software among construction industry players in Malaysia is still low and among the obstacles that occur is the construction industry players in Malaysia are mostly still not open to accept new methods and still rely on traditional methods in implementing construction projects. It is also shows the effectiveness of the application of Autodesk Revit software in the construction industry in Malaysia still need to be improved and hopefully Malaysia can get lots of benefits when BIM is fully appreciated.